Influence of age on the effectiveness and duration of protection of Vaxzevria and CoronaVac vaccines: A population-based study - Thiago Cerqueira-Silva; Vinicius de Araújo Oliveira; Viviane S. Boaventura; Julia M. Pescarini; Juracy Bertoldo Júnior; Tales Mota Machado; Renzo Flores-Ortiz; Gerson O. Penna; Maria Yury Ichihara; Jacson Venâncio de Barros; Mauricio L. Barreto; Guilherme Loureiro Werneck; et al. (Elsevier, 2022)
Summary: Background: Aging influences COVID-19 severity and response to vaccination, but previous vaccine effectiveness (VE) analyzes lack the power to evaluate its role in subgroups within the elderly age group. Here we analyzed the impact of age on viral vector and inactivated virus vaccines' effectiveness, the main platforms used in low- and middle-income countries. Methods: We report a retrospective longitudinal study of 75,919,840 Brazilian vaccinees from January 18 to July 24, 2021, evaluating documented infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), COVID-19-related hospitalisation, ICU admission, and death. Negative binomial regression models adjusted for sociodemographic characteristics were used for VE estimation. Findings: The overall analyzes of full vaccination showed VE against hospitalisation, ICU admission, and death of 91·4% (95%CI:90·1-92·5), 91·1% (95%CI:88·9-92·9) and 92·3% (95%CI:90·5-93·7) for Vaxzevria and 71·2% (95%CI:70·0-72·4), 72·2% (95%CI:70·2-74·0) and 73·7% (95%CI:72·1-75·2) for CoronaVac, respectively. VE for all outcomes is progressively lower with age. In fully-Vaxzevria-vaccinated individuals aged <60 years, VE against death was 96.5% (95%CI:82.1-99.3) versus 68·5% (95%CI:40·0-83·4) in those ≥90 years. Among fully-CoronaVac-vaccinated individuals, VE against death was 84.8% (95%CI:77.1-89.9) in those <60 years compared to 63.5 (95%CI 58.7-67.7) for vaccinees aged 80-89 years and 48·6%; (95%CI:35·0-59·3) for individuals aged ≥90 years. Post-vaccination daily cumulative incidence curves for all outcomes showed increased risk from younger to elder decades of life. There was no increase in the incidence of hospitalisation for individuals <60 years vaccinated during the same period as those aged ≥90 years. Interpretation: Although both vaccines have been effective in protecting against infection, hospitalization and death; Vaxzevria and CoronaVac demonstrated high effectiveness against severe outcomes for individuals up to 79 years of age. Our results reinforce the idea that booster doses should be carefully considered in elders. Funding: This study was partially supported by a donation from the ''Fazer o bem faz bem'' program.